Extent of Left Atrial Ablation Lesions and Atrial Fibrillation Recurrence after Catheter Ablation - A Systematic Review and Meta-Analysis - Correia,Eduardo Thadeu de Oliveira (2020)
Abstract Background: Atrial fibrillation (AF) is known to induce atrial remodeling, which promotes fibrosis related to arrhythmogenesis. Accordingly, since scars induced by catheter ablation (CA) can reduce unablated fibrotic areas, greater extent of left atrial (LA) scarring may be associated with less AF recurrence after CA. Objectives: This study aims to investigate, through systematic review and meta-analysis, whether the amount of LA scarring, seen on late gadolinium enhancement magnetic resonance imaging, is associated with less AF recurrence after CA. Methods: The recommendations of the MOOSE guideline were followed. Database search was conducted in PubMed and Cochrane Central Register of Controlled Trials (comentário 1) until January 2019 (comentário 2). Two authors performed screening, data extraction, and quality evaluation. All studies were graded as good quality. A funnel plot was generated, showing no publication bias. Statistical significance was defined as p value < 0.05. Results: Eight observational studies were included in the systematic review, four of which were included in the meta-analysis. Six of the eight studies included in the systematic review showed that greater extension of LA scarring is associated with less AF recurrence after CA. Meta-analysis showed that greater extension of LA scarring is associated with less AF recurrence (SMD = 0.52; 95% CI 0.27 - 0.76; p < 0.0001). Conclusion: Greater extension of LA scarring is possibly associated with less AF recurrence after CA. Randomized studies that explore ablation methods based on this association are fundamental.